PENGARUH VARIASI BERAT RESIN ION EXCHANGE TERHADAP PENURUNAN pH AIR LIMBAH PRODUKSI DI PT. XYZ (Jurnal Kesehatan Siliwangi, 2021)
One of the problems experienced by PT. XYZ is the high pH value of ineligible production wastewater. One way to reduce pH is by the ion exchange method. This research aims to determine the variation in the weight of ion exchanger resins (anion exchangers) in ion exchange installations against the decrease in wastewater pH. This type of research is experimental research. The treatment used is a variation in the weight of anion resin 250 gr, 300 gr and 350 gr. The research population is all wastewater production at PT. XYZ. The sample in this research is part of wastewater production as much as 141.3 liters for 18 treatments (6 treatments per variation). Sampling techniques are done by grab sampling. Data collection techniques are carried out by means of measurement and laboratory examination. Data analysis was conducted using univariate test and bivariate test in the form of One Way Anova test. The sample in this research is part of wastewater production as much as 141.3 liters for 18 treatments (6 treatments per variation). Sampling techniques are done by grab sampling. Data collection techniques are carried out by means of measurement and laboratory examination. Data analysis was conducted using univariate test and bivariate test in the form of One Way Anova test. The results showed that there were differences in various variations in resin weight in the decrease in wastewater pH production, whereas P value < α (0.03 < 0.05).